Grazing management plan adoption in the United States beef industry - Kniebel Aherin, Cassandra (Kansas State University, 2021)
This research focuses on the adoption and use of grazing management plans across the United States. The emphasis on sustainability has increased in the last several years across multiple food supply chains, and the United States beef supply chain is no exception. Through efforts from multiple stakeholders, including cattle producers, and from organizations like the U.S. Roundtable for Sustainable Beef, benchmarks and metrics are being established across prioritized indicators for sectors throughout the cattle and beef value chain. Grazing management plans have been identified as one of the tools useful for monitoring and measuring an operation’s progress towards sustainability goals due to their ability to influence land, water, and air and greenhouse gas indicators. The main objective of this study is to determine the adoption baseline of cattle grazing management plans in the United States and evaluate the potential characteristics influencing the adoption of these plans. An electronic survey is used to collect data from cattle producers across the United States. Descriptive statistics are used to assess the baseline of adoption and a binary logit model analyzed the influential factors in adopting a grazing management plan. Producer age, primary decision maker classification, operation location and type, herd size, grazing acreage size, land ownership classification, and succession planning are all factors that were included in the assessment. Most influential to the decision-making process for producers are age (written grazing management plans only), size of operation in terms of grazing acres, and succession planning. Stocker operation size and the primary decision-making role seem to influence the adoption of a grazing management plan as well. In terms of written grazing management plan adoption across the U.S. cattle industry, about 43 percent indicate they do have one, while 56 percent say they do not have a plan. This study shows the industry is on their way to meeting the sustainability standards set by various organizations and stakeholders. However, additional resources need to be developed and promoted across the industry to further encourage adoption of written plans and improve the robustness of detail included, as well as the constant evaluation and adjustment of the plans over time.
Keywords: Grazing management; Sustainabilty; Cattle; Agricultural economics; Stocker operation